USE OF HERSCEL-BUCKLEY MODEL FOR THE PREDICTION OF GROUT PROPAGATION IN POROUS MEDIA AND COMPARISON WITH IN SITU RESULTS - Χατζηαγγέλου, M.; Αναγνωστόπουλος, Κ. (Bulletin of the Geological Society of Greece, 2004)
Grouting as a mean to strengthen weak soils or rock mass for construction foundations or underground facilities has been used for decades. With an increased demand for technical efficiency and cost reduction, the need to improve the method has also increased. The know-how of grouting relates to several fields of research, for instance flow in porous media and the behaviour of grouting research. In this paper, a grout propagation prediction model in porous media is studied with the use of Herscel-Buckley law. Continuously, a comparison between the results of prediction model and those derived from cement grouting during the excavation of a tunnel in a weathering rock mass, is carried out.